The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.18632/oncotarget.25173
|View full text |Cite
|
Sign up to set email alerts
|

MiR-33 promotes myocardial fibrosis by inhibiting MMP16 and stimulating p38 MAPK signaling

Abstract: Myocardial fibrosis occurs in the late stages of many cardiovascular diseases, and appears to be stimulated by various microRNAs (miRNAs). We previously found that miR-33 may stimulate cardiac remodeling. Here, we examined the involvement of miR-33 in myocardial fibrosis. Proximal left coronary descending artery occlusion was performed in rat, and antagomiR-33a was injected. Primary cardiac fibroblasts were cultured and transfected with miR-33a mimics and inhibitors. miR-33a levels were increased in the rat af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…SPP1, a protein with proinflammatory and profibrotic properties, has already been demonstrated to take part in cardiac and lung fibrosis 59,60 . MMP16 protein activates MMP2 protein which in turn degrades type III collagen and was demonstrated to be decreased in the myocardial fibrosis 61 .…”
Section: Resultsmentioning
confidence: 99%
“…SPP1, a protein with proinflammatory and profibrotic properties, has already been demonstrated to take part in cardiac and lung fibrosis 59,60 . MMP16 protein activates MMP2 protein which in turn degrades type III collagen and was demonstrated to be decreased in the myocardial fibrosis 61 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is possible that interaction with other RNA‐binding proteins and miRNAs may play a role in regulating the stability of ECM marker mRNAs or that HuR is controlling translation. Further support for these possibilities comes from a study in cardiac fibroblasts, where miR‐33a increases the expression of COL1A1 and COL3A1 (in vivo and in vitro) and that knockdown of miR‐33a is sufficient to decrease their expression (Chen et al, 2018). This effect of miR‐33a on COL1A1 and COL3A1 expression is mediated through the p38 MAPK pathway but not through the TGFβ1/SMAD pathway (Chen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Four of these 6 miRNAs identified only in the I/R+CRP group (miR-33, miR-409-3p, miR-384-3p and miR-101a) were found to be involved in myocardial disease. Recent studies have shown that the expression level of miR-33 is elevated in heart failure [31] and that miR-33 promotes myocardial fibrosis [32] and vascular atherosclerosis [33]. Currently, miR-33 is being considered as a new therapeutic target [34].…”
Section: Discussionmentioning
confidence: 99%